Formation of coke during the pyrolysis of bio-oil - Wang, Yi; Mourant, Daniel; Hu, Xun; Zhang, Shu; Lievens, Caroline; Li, Chun-Zhu (Elsevier Ltd, 2013)
Bio-oil from the pyrolysis of biomass can be upgraded into high quality liquid biofuels or utilised as a feedstock to boilers and gasifiers. The coke formation is a particularly serious problem for the upgrading of bio-oil as well as the direct utilisation of bio-oil. The effects of bio-oil chemical composition on the coke formation are keys to the understanding of the mechanism of coke formation. A bio-oil sample produced from the fast pyrolysis of mallee wood at 500 °C and the lignin-derived oligomers separated from the bio-oil were pyrolysed in a two-stage fluidised-bed/fixed-bed reactor at temperatures between 250 and 800 °C. In addition to the quantification of coke yield, UV-fluorescence spectroscopy was used to trace the formation and evolution of aromatic ring systems during pyrolysis. Our results indicate that both water-soluble and water-insoluble bio-oil fractions can form coke even at very low temperatures. The interactions among the species derived from cellulose/hemicellulose and lignin, especially the interactions involving their oligomers, are important to the observed coke yield, especially at low temperatures.